2012
DOI: 10.1021/ja210847n
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Reactions of Ketones and Thioketones with Alkyllithiums: A Coordinated Experimental and Computational Investigation

Abstract: The reaction of ketones with organolithium reagents generally proceeds by addition of the organometallic to the electrophilic carbon of the C═O group to give the lithium salt of a tertiary alcohol. The seemingly analogous reaction of thioketones with organolithiums is a fundamentally different process: such reactions typically afford a variety of products, and addition of the organolithium to carbon of the C═S group to give a thiol is a relatively unimportant component. Reactions of the stable thioketone, adam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…While for ketones, the main product results from addition to the carbonyl carbon, thioketones tend to undergo addition to sulfur or reduction of the C-S double bond [125]. In their study, TSs for addition to thioketones were found to require a higher activation barrier than the corresponding TSs for ketone addition, in fine agreement with their observations.…”
Section: Computational Studies On Various Organolithium Applicationssupporting
confidence: 75%
“…While for ketones, the main product results from addition to the carbonyl carbon, thioketones tend to undergo addition to sulfur or reduction of the C-S double bond [125]. In their study, TSs for addition to thioketones were found to require a higher activation barrier than the corresponding TSs for ketone addition, in fine agreement with their observations.…”
Section: Computational Studies On Various Organolithium Applicationssupporting
confidence: 75%
“…This reaction presents an alternative approach for the synthesis of 2,3-dicarbonylpyrrole derivatives. , In contrast with the construction of 88 , in the synthesis of 95 with N -methylprop-2-yn-1-amine as the amine component, the thiophilic nucleophilic reaction , for formation of thiiranium intermediate 98 , (also see Scheme ) should be critical for the formation of 95 via 1,2-acyl migration (Scheme ). …”
Section: Heteroannulation Reactions Via Ketene Ns-acetalsmentioning
confidence: 99%
“…Hydrolysis gave the corresponding thioethers 6 (see the Supporting Information). Such a 1,2‐addition of organolithium reagents to thiocarbonyl compounds—with inverse selectivity compared to carbonyl compounds—has only recently been noticed . However, the high selectivity of the reactions with thio‐ 1 and thio‐ 2 is remarkable.…”
Section: Figurementioning
confidence: 99%
“…Such a1 ,2-addition of organolithium reagents to thiocarbonyl compounds-with inverse selectivity comparedt oc arbonyl compounds-has only recently been noticed. [33] However,t he high selectivity of the reactions with thio-1 and thio-2 is remarkable. This reverse 1,2-addition is also in line with the formation of the cyclization products 3 and 4,i nw hich the carbenoid itself selectively adds to the C=Sbond.…”
mentioning
confidence: 99%